ANALISIS HUKUM PEMUTUSAN HUBUNGAN KERJA TERHADAP KARYAWAN KARENA KONSUMSI TUAK DALAM PERSPEKTIF KETENAGAKERJAAN INDONESIA - Syahyunan, Hengki; Zelibu, Yanto; Siregar, Putri Habibah; Ritonga, Muhammad Khoirul; Siregar, Ahmad Ansyari (Universitas Labuhanbatu, 2025)
Termination of Employment is a legal action that may be undertaken by an employer against an employee under certain conditions, including violations of workplace discipline. One controversial case involves the dismissal of an employee found consuming tuak (a traditional alcoholic beverage). This study aims to analyze the legal aspects of such termination based on Indonesian labor regulations and contributes to a broader understanding of cultural context in the enforcement of labor law in Indonesia. The research employs a normative juridical approach, using literature review and case analysis. The findings indicate that termination of employment due to the consumption of tuak can only be legally justified if the act occurred during working hours, within the workplace, or demonstrably affected job performance and workplace safety. Termination is deemed unlawful if it does not follow the prescribed procedures or lacks sufficient evidence of serious misconduct as stipulated in the company's internal regulations. Therefore, any termination decision must take into account the principles of fairness, proportionality, and legal certainty for both parties.Keywords: Tuak; Company; Termination of Employment